Carbon nanomaterial-based composite conductive paste for lithium battery and preparation method of carbon nanomaterial-based composite conductive paste
By using a circulating emulsification pump and grinding device in the lithium battery conductive paste, and mixing it with single-wall carbon nanotubes to prepare composite conductive paste, the problems of degradation of graphene and difficulty in dispersion are solved, and the formation of an efficient conductive network and the improvement of lithium battery performance are achieved.
Patent Information
- Application Number
- CN202411986087.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-11
AI Technical Summary
In the existing lithium battery conductive paste, the conductive properties of graphene are damaged, and nanoscale graphene is difficult to effectively disperse in the active materials of lithium battery, resulting in the inability to fully exert the conductive function.
A composite conductive paste based on carbon nanomaterial for lithium batteries is used to process scale graphite through a circulating emulsification pump and a grinding device to form graphene microsheets, and mixed with single-wall carbon nanotubes to prepare the composite conductive paste by homogenization and ultrasonic dispersion.
Maximize the structural integrity of single-wall carbon nanotubes, form an efficient conductive network, improve contact between active material particles, enhance conductivity, improve the capacity and rate performance of lithium batteries, extend cycle life and reduce interface impedance.
Smart Images

Figure BDA0005222611410000091 
Figure BDA0005222611410000101
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of conductive pastes, and in particular to a carbon nanomaterial-based composite conductive paste for lithium batteries and a preparation method thereof. Background Art
[0002] Lithium batteries are widely used in various electronic products due to their excellent performance, and the conductive paste of lithium batteries is the carrier of ion transmission in the battery and is an indispensable and important component of lithium batteries. At present, the mass production method of graphene is to prepare it through the redox method. The prepared graphene oxide suspension solution is then atomized and reduced to finally obtain graphene powder. However, the surface of the graphene obtained by redox contains a large number of functional groups, and the structure and performance of the graphene are also destroyed. In addition, the sheet structure of graphene will also be damaged during the preparation process, resulting in a decrease in the conductivity of graphene, which affects the performance of the conductivity of graphene. In addition, since the size of graphene reaches the nanoscale, the agglomeration between its particles makes it difficult to effectively disperse it in the active material of the lithium battery, and it is difficult to establish an efficient conductive channel, which makes it difficult to fully exert the conductive function of graphene. Summary of the invention
[0003] In view of this, the present invention provides a carbon nanomaterial-based composite conductive slurry for lithium batteries and a preparation method thereof to solve the above-mentioned problems.
[0004] The technical solution adopted by the present invention to solve its technical problem is:
[0005] A carbon nanomaterial-based composite conductive slurry for lithium batteries. The raw materials, measured by weight, include: 5-10 parts of flake graphite, 5-10 parts of single-walled carbon nanotubes, 0.5-1 part of dispersant, 0.3-0.6 part of accelerator, 0.1-0.3 part of viscosity regulator, and 75-90 parts of solvent.
[0006] Furthermore, the single-walled carbon nanotube has a diameter of 0.1 to 3 nm and a length of 1 to 4 μm.
[0007] Furthermore, the dispersant includes at least one of nonylphenol polyoxyethylene ether, isononyl alcohol polyoxyethylene ether, and lauryl alcohol polyoxyethylene ether.
[0008] Furthermore, the solvent is at least one of N-methylpyrrolidone, N-ethylpyrrolidone, N,N-dimethylformamide, ethanol, and deionized water.
[0009] Furthermore, the accelerator is at least one of polyvinyl alcohol, polyethylene glycol, and polyvinyl pyrrolidone.
[0010] Furthermore, the viscosity modifier is at least one of carboxymethyl cellulose, hydroxyethyl cellulose and hypromellose.
[0011] Furthermore, the method for preparing the carbon nanomaterial-based composite conductive paste for lithium batteries is characterized by comprising the following preparation steps:
[0012] (1) weighing flake graphite, single-walled carbon nanotubes, dispersant, promoter, viscosity modifier and solvent according to the formula amount;
[0013] (2) adding flake graphite and a dispersant to a portion of the solvent and stirring and mixing to obtain a mixed material;
[0014] (3) conveying the mixed material to a circulating emulsification pump, and using the circulating emulsification pump to emulsify and premix the mixed material, so that the flake graphite in the mixed material is peeled off under the action of the circulating emulsification pump to form multi-layer graphite sheets, thereby obtaining a premixed dispersion;
[0015] (4) conveying the premixed dispersion to a grinding device for grinding and dispersion, grinding the multilayer graphite sheets in the premixed dispersion by the grinding device so that the multilayer graphite sheets are gradually peeled off to form graphene microsheets, thereby obtaining a grinding dispersion;
[0016] (5) adding single-walled carbon nanotubes, a promoter, a viscosity modifier and the remaining solvent to the grinding dispersion, stirring evenly and then conveying to a homogenizer for emulsification and homogenization, and generating high-frequency, strong circumferential tangential velocity, angular velocity and other comprehensive kinetic energy through the high-speed and stable rotation of the rotor in the homogenizer, thereby exfoliating the graphene microsheets in the grinding dispersion to form few-layer graphene, and dispersing the single-walled carbon nanotubes to obtain a crude conductive slurry;
[0017] (6) placing the crude conductive slurry in an ultrasonic disperser for ultrasonic dispersion, and then performing demagnetization and purification treatment using an electromagnetic filtration device to obtain a carbon nanomaterial-based composite conductive slurry for lithium batteries.
[0018] Furthermore, the grinding device in step (4) includes at least one of a stirring grinder, a sand mill, and a planetary ball mill.
[0019] Furthermore, the ultrasonic dispersion conditions in step (6) are a frequency of 100 to 120 kHz and a power of 1000 to 1500 W.
[0020] The beneficial effects of the present invention are:
[0021] The present invention uses flake graphite as a raw material, first grinds it through a circulating emulsifying pump and a grinding device to form graphene microsheets, and then mixes it with single-walled carbon nanotubes to prepare a composite conductive slurry through homogenization and ultrasonic dispersion. This can reduce the grinding and shearing process of the single-walled carbon nanotubes and retain the structural integrity of the single-walled carbon nanotubes to the maximum extent. The single-walled carbon nanotubes are in a hollow cylindrical shape. This fiber-like structure can form point-to-line contact with the active material of the electrode material, and can act as a "wire" in the conductive network to increase the contact between the active material particles, thereby exerting high-rate characteristics. In addition, carbon tubes have excellent mechanical properties and chemical stability. The conductive network they form can reduce the increase in resistance caused by the volume shrinkage and expansion of the positive electrode particles during the charge and discharge process of the battery, which is beneficial to improve the battery capacity and rate performance, extend the cycle life of the battery, and reduce the battery interface impedance; flake graphite is gradually peeled off under the action of multiple grinding and dispersion treatment processes to form a few layers of graphene. Graphene has a unique two-dimensional sheet structure, and the contact with the active material is point-to-surface contact, presenting a semi-enclosed type. This conductive network can maximize the role of the conductive agent and reduce the proportion of the conductive agent, thereby increasing the use of electrode active materials, increasing the capacity of the lithium battery while quickly conducting heat, reducing the battery's heating rate, and improving the battery's safety. DETAILED DESCRIPTION
[0022] The present invention is further described in detail below in conjunction with specific embodiments, but the embodiments of the present invention are not limited thereto. For process parameters not particularly noted, conventional techniques may be used.
[0023] The present invention provides a method for preparing a carbon nanomaterial-based composite conductive slurry for a lithium battery, comprising the following steps:
[0024] (1) According to the weight ratio, 5 to 10 parts of flake graphite, 5 to 10 parts of single-walled carbon nanotubes with a diameter of 0.1 to 3 nm and a length of 1 to 4 μm, 0.5 to 1 part of a dispersant, 0.3 to 0.6 parts of an accelerator, 0.1 to 0.3 parts of a viscosity modifier, and 75 to 90 parts of a solvent are weighed respectively;
[0025] (2) adding flake graphite and a dispersant to a portion of the solvent and stirring and mixing to obtain a mixed material;
[0026] (3) conveying the mixed material to a circulating emulsification pump, and using the circulating emulsification pump to emulsify and premix the mixed material, so that the flake graphite in the mixed material is peeled off under the action of the circulating emulsification pump to form multi-layer graphite sheets, thereby obtaining a premixed dispersion;
[0027] (4) conveying the premixed dispersion to a grinding device for grinding and dispersion, grinding the multilayer graphite sheets in the premixed dispersion by the grinding device so that the multilayer graphite sheets are gradually peeled off to form graphene microsheets, thereby obtaining a grinding dispersion;
[0028] (5) adding single-walled carbon nanotubes, a promoter, a viscosity modifier and the remaining solvent to the grinding dispersion, stirring evenly and then conveying to a homogenizer for emulsification and homogenization, and generating high-frequency, strong circumferential tangential velocity, angular velocity and other comprehensive kinetic energy through the high-speed and stable rotation of the rotor in the homogenizer, thereby exfoliating the graphene microsheets in the grinding dispersion to form few-layer graphene, and dispersing the single-walled carbon nanotubes to obtain a crude conductive slurry;
[0029] (6) The crude conductive slurry is placed in an ultrasonic disperser and ultrasonically dispersed at a frequency of 100 to 120 kHz and a power of 1000 to 1500 W, and then demagnetized and purified using an electromagnetic filtration device to obtain a carbon nanomaterial-based composite conductive slurry for lithium batteries.
[0030] Wherein, the dispersant is at least one of nonylphenol polyoxyethylene ether, isononyl alcohol polyoxyethylene ether, and lauryl alcohol polyoxyethylene ether; the solvent is at least one of N-methylpyrrolidone, N-ethylpyrrolidone, N,N-dimethylformamide, ethanol, and deionized water; the accelerator is at least one of polyvinyl alcohol, polyethylene glycol, and polyvinyl pyrrolidone; the viscosity modifier is at least one of carboxymethyl cellulose, hydroxyethyl cellulose, and hydroxypropyl methylcellulose; and the grinding device includes at least one of a stirred grinder, a sand mill, and a planetary ball mill.
[0031] Example 1
[0032] The method for preparing a carbon nanomaterial-based composite conductive slurry for a lithium battery of the present embodiment comprises the following steps:
[0033] (1) According to the weight percentage, 5 parts of flake graphite, 5 parts of single-walled carbon nanotubes with a diameter of 0.1 nm and a length of 1 μm, 0.5 parts of nonylphenol polyoxyethylene ether, 0.3 parts of polyvinyl alcohol, 0.1 parts of carboxymethyl cellulose, and 75 parts of N-methylpyrrolidone were weighed respectively;
[0034] (2) adding flake graphite and nonylphenol polyoxyethylene ether to a portion of the solvent and stirring and mixing to obtain a mixed material;
[0035] (3) conveying the mixed material to a circulating emulsification pump, and using the circulating emulsification pump to emulsify and premix the mixed material, so that the flake graphite in the mixed material is peeled off under the action of the circulating emulsification pump to form multi-layer graphite sheets, thereby obtaining a premixed dispersion;
[0036] (4) conveying the premixed dispersion to a stirring mill for grinding and dispersion, grinding the multilayer graphite sheets in the premixed dispersion by the stirring mill so that the multilayer graphite sheets are gradually peeled off to form graphene microsheets, thereby obtaining a grinding dispersion;
[0037] (5) adding single-walled carbon nanotubes, polyvinyl alcohol, carboxymethyl cellulose and the remaining solvent to the grinding dispersion, stirring evenly and then conveying to a homogenizer for emulsification and homogenization, and generating high-frequency, strong circumferential tangential velocity, angular velocity and other comprehensive kinetic energy through the high-speed and stable rotation of the rotor in the homogenizer, thereby exfoliating the graphene microsheets in the grinding dispersion to form few-layer graphene, and dispersing the single-walled carbon nanotubes to obtain a crude conductive slurry;
[0038] (6) The crude conductive slurry is placed in an ultrasonic disperser and ultrasonically dispersed at a frequency of 100 kHz and a power of 1000 W, and then demagnetized and purified using an electromagnetic filtration device to obtain a carbon nanomaterial-based composite conductive slurry for lithium batteries.
[0039] Example 2
[0040] The method for preparing a carbon nanomaterial-based composite conductive slurry for a lithium battery of the present embodiment comprises the following steps:
[0041] (1) According to the weight percentage, 7 parts of flake graphite, 7 parts of single-walled carbon nanotubes with a diameter of 1 nm and a length of 2 μm, 0.7 parts of polyoxyethylene isononyl alcohol ether, 0.4 parts of polyethylene glycol, 0.2 parts of hydroxyethyl cellulose, and 80 parts of N-ethylpyrrolidone were weighed respectively;
[0042] (2) adding flake graphite and isononyl alcohol polyoxyethylene ether to a portion of N-ethyl pyrrolidone and stirring and mixing to obtain a mixed material;
[0043] (3) conveying the mixed material to a circulating emulsification pump, and using the circulating emulsification pump to emulsify and premix the mixed material, so that the flake graphite in the mixed material is peeled off under the action of the circulating emulsification pump to form multi-layer graphite sheets, thereby obtaining a premixed dispersion;
[0044] (4) conveying the premixed dispersion to a sand mill for grinding and dispersion, grinding the multilayer graphite sheets in the premixed dispersion by the sand mill so that the multilayer graphite sheets are gradually peeled off to form graphene microsheets, thereby obtaining a grinding dispersion;
[0045] (5) adding single-walled carbon nanotubes, polyethylene glycol, hydroxyethyl cellulose and remaining N-ethylpyrrolidone to the grinding dispersion, stirring evenly and then conveying to a homogenizer for emulsification and homogenization, and generating high-frequency, strong circumferential tangential velocity, angular velocity and other comprehensive kinetic energy through the high-speed and stable rotation of the rotor in the homogenizer, thereby exfoliating the graphene microsheets in the grinding dispersion to form few-layer graphene, and dispersing the single-walled carbon nanotubes to obtain a crude conductive slurry;
[0046] (6) The crude conductive slurry is placed in an ultrasonic disperser and ultrasonically dispersed at a frequency of 110 kHz and a power of 1200 W, and then demagnetized and purified using an electromagnetic filtration device to obtain a carbon nanomaterial-based composite conductive slurry for lithium batteries.
[0047] Example 3
[0048] The method for preparing a carbon nanomaterial-based composite conductive slurry for a lithium battery of the present embodiment comprises the following steps:
[0049] (1) According to the weight percentage, 10 parts of flake graphite, 10 parts of single-walled carbon nanotubes with a diameter of 3 nm and a length of 4 μm, 1 part of polyoxyethylene lauryl alcohol ether, 0.6 parts of polyvinyl pyrrolidone, 0.3 parts of hydroxypropyl methylcellulose, and 90 parts of N,N-dimethylformamide were weighed respectively;
[0050] (2) adding flake graphite and lauryl alcohol polyoxyethylene ether to a portion of N,N-dimethylformamide and stirring and mixing to obtain a mixed material;
[0051] (3) conveying the mixed material to a circulating emulsification pump, and using the circulating emulsification pump to emulsify and premix the mixed material, so that the flake graphite in the mixed material is peeled off under the action of the circulating emulsification pump to form multi-layer graphite sheets, thereby obtaining a premixed dispersion;
[0052] (4) conveying the premixed dispersion to a planetary ball mill for grinding and dispersion, grinding the multilayer graphite sheets in the premixed dispersion by the planetary ball mill so that the multilayer graphite sheets are gradually peeled off to form graphene microsheets, thereby obtaining a grinding dispersion;
[0053] (5) adding single-walled carbon nanotubes, polyvinyl pyrrolidone, hydroxypropyl methylcellulose and remaining N,N-dimethylformamide to the grinding dispersion, stirring evenly and then conveying to a homogenizer for emulsification and homogenization, and generating high-frequency, strong circumferential tangential velocity, angular velocity and other comprehensive kinetic energy through the high-speed and stable rotation of the rotor in the homogenizer, thereby exfoliating the graphene microsheets in the grinding dispersion to form few-layer graphene, and dispersing the single-walled carbon nanotubes to obtain a crude conductive slurry;
[0054] (6) The crude conductive slurry is placed in an ultrasonic disperser and ultrasonically dispersed at a frequency of 120 kHz and a power of 1500 W, and then demagnetized and purified using an electromagnetic filtration device to obtain a carbon nanomaterial-based composite conductive slurry for lithium batteries.
[0055] Comparative Example
[0056] Conductive paste products produced and sold by a company in Qingdao.
[0057] Experimental example
[0058] Resistivity measurement: The conductive slurry samples prepared in Examples 1 to 3 and the conductive slurry samples of the comparative example were homogenized and then coated on a Pl film substrate with a specification of 30 cm*20 cm. The coated substrate was placed in an oven for drying and then the sample was tested. 5 cm was cut off from each end of the substrate and tested with a four-probe tester. Nine points were taken in the middle according to a nine-square grid for testing and recording, and the average value was calculated.
[0059] Conductivity measurement: The conductive paste samples prepared in Examples 1 to 3 and the conductive paste samples of the comparative example were dried and subjected to a flat vulcanizer (pressure 5 MPa, pressure holding for 3 min) to obtain discs with a diameter of 25.4 mm. The resistivity was then tested using a four-probe SX1934 (SZ-82) model, and the conductivity of the conductive pastes prepared in Examples 1 to 3 and the conductive pastes of the comparative example was converted.
[0060] Viscosity measurement: The conductive paste samples prepared in Examples 1 to 3 and the conductive paste samples of the comparative example were tested using a NDJ-8S digital rotational viscometer.
[0061] The specific test results are shown in Table 1.
[0062] Table 1: Statistical table of various parameters of conductive paste samples of Examples 1 to 3 and Comparative Examples
[0063]
[0064]
[0065] As can be seen from Table 1, the resistivity of the conductive pastes prepared in Examples 1 to 3 is less than that of the comparative example, and the conductivity of the conductive pastes prepared in Examples 1 to 3 is greater than that of the comparative example. Therefore, the conductive paste preparation process of the present invention can reduce the grinding and shearing process of single-walled carbon nanotubes, retain the structural integrity of single-walled carbon nanotubes to the maximum extent, so that they act as "wires" in the conductive network, increase the contact between active material particles, and thus improve the conductivity; at the same time, the flake graphite is gradually peeled off under the action of multiple grinding and dispersion processes to form a few layers of graphene and is evenly dispersed in the conductive paste, thereby maximizing the role of the conductive agent, reducing the resistivity of the conductive paste while improving the conductivity. Therefore, the graphene single-walled carbon nanotube conductive paste prepared by the present invention has excellent electrical conductivity and has broad application prospects in the field of new energy batteries.
[0066] Based on the above ideal embodiments of the present invention, the relevant staff can make various changes and modifications without departing from the scope of the present invention through the above description. The technical scope of this invention is not limited to the contents of the specification, and its technical scope must be determined according to the scope of the claims.
Claims
1. A carbon nanomaterial-based composite conductive slurry for lithium batteries, characterized in that: The raw materials include, by weight: 5-10 parts of flake graphite, 5-10 parts of single-walled carbon nanotubes, 0.5-1 part of dispersant, 0.3-0.6 part of promoter, 0.1-0.3 part of viscosity regulator and 75-90 parts of solvent.
2. The carbon nanomaterial-based composite conductive paste for lithium batteries according to claim 1, characterized in that: The single-walled carbon nanotube has a diameter of 0.1 to 3 nm and a length of 1 to 4 μm.
3. The carbon nanomaterial-based composite conductive paste for lithium batteries according to claim 1, characterized in that: The dispersant includes at least one of nonylphenol polyoxyethylene ether, isononyl alcohol polyoxyethylene ether and lauryl alcohol polyoxyethylene ether.
4. The carbon nanomaterial-based composite conductive paste for lithium batteries according to claim 1, characterized in that: The solvent is at least one of N-methylpyrrolidone, N-ethylpyrrolidone, N,N-dimethylformamide, ethanol and deionized water.
5. The carbon nanomaterial-based composite conductive paste for lithium battery according to claim 1, characterized in that: The accelerator is at least one of polyvinyl alcohol, polyethylene glycol and polyvinyl pyrrolidone.
6. The carbon nanomaterial-based composite conductive paste for lithium batteries according to claim 1, characterized in that: The viscosity modifier is at least one of carboxymethyl cellulose, hydroxyethyl cellulose and hypromellose.
7. A method for preparing the carbon nanomaterial-based composite conductive slurry for lithium batteries as claimed in claims 1 to 6, characterized in that: The method comprises the following preparation steps: (1) weighing flake graphite, single-walled carbon nanotubes, dispersant, promoter, viscosity modifier and solvent according to the formula amount; (2) adding flake graphite and a dispersant to a portion of the solvent and stirring and mixing to obtain a mixed material; (3) conveying the mixed material to a circulating emulsification pump, and using the circulating emulsification pump to emulsify and premix the mixed material, so that the flake graphite in the mixed material is peeled off under the action of the circulating emulsification pump to form multi-layer graphite sheets, thereby obtaining a premixed dispersion; (4) conveying the premixed dispersion to a grinding device for grinding and dispersion, grinding the multilayer graphite sheets in the premixed dispersion by the grinding device so that the multilayer graphite sheets are gradually peeled off to form graphene microsheets, thereby obtaining a grinding dispersion; (5) adding single-walled carbon nanotubes, a promoter, a viscosity modifier and the remaining solvent to the grinding dispersion, stirring evenly and then conveying to a homogenizer for emulsification and homogenization, and generating high-frequency, strong circumferential tangential velocity, angular velocity and other comprehensive kinetic energy through the high-speed and stable rotation of the rotor in the homogenizer, thereby exfoliating the graphene microsheets in the grinding dispersion to form few-layer graphene, and dispersing the single-walled carbon nanotubes to obtain a crude conductive slurry; (6) placing the crude conductive slurry in an ultrasonic disperser for ultrasonic dispersion, and then performing demagnetization and purification treatment using an electromagnetic filtration device to obtain a carbon nanomaterial-based composite conductive slurry for lithium batteries.
8. The method for preparing a carbon nanomaterial-based composite conductive paste for lithium batteries according to claim 7, characterized in that: The grinding device in step (4) includes at least one of a stirring grinder, a sand mill, and a planetary ball mill.
9. The method for preparing a carbon nanomaterial-based composite conductive paste for lithium batteries according to claim 7, characterized in that: The ultrasonic dispersion conditions in step (6) are a frequency of 100 to 120 kHz and a power of 1000 to 1500 W.